Interruption of informality in artisanal cachaça: an analysis from the perspective of institutional work - Morais, Raphael de; Brito , Valéria da Glória Pereira; Brito, Mozar José de; Pinheiro, Daniel Calbino (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
Informality presents itself as one of the hallmarks of the still cachaça. In the state of Minas Gerais, the largest artisanal producer in the country, the rates surpassed 98% in 1980. Based on the perspective of institutional work, the objective of this article was to understand how the practices of the managers of the National Association of Producers took place in interrupting informality. In methodological terms, a qualitative study was used, investigating three decades of institutional practices. It was found that if deinstitutionalization reduced informality, the challenges have not been exhausted, since legal structures are still an obstacle for the sector. The results contribute with empirical elements that reinforce the disruption, in a theoretical context still little explored in the literature.